Aspek-Aspek Teologi Islam dalam Pernikahan Tradisi Mepahukh Masyarakat di Desa Darul Amin, Kecamatan Lawe Alas, Kabupaten Aceh Tenggara - Armin Nasution; Ratna Sahpitri (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Abstract. Religion is a religion which kaffah covers all fields of science including Islamic Theology, Sociology, Tawheed and Philosophy, culture and customs are no exception. Talking about marriage and traditions, the people of Kutacane, especially those in Darul Amin village, are very famous for their very strong customs and culture. The mepahukh tradition is a custom carried out by young people and girls after the wedding ceremony. The problem in this study is how the process and what is the importance of this mepahukh tradition to be carried out.This research uses qualitative methods by means of observation and interviews as well as literature study, a research approach that uses a religious approach, the purpose of this research is to find out and will try to describe why the traditional marriage or mepahukh tradition in the community in Darul Amin village has been maintained until now. The results of this study indicate that the mepahukh tradition has procedures that have been determined by custom in the process of carrying it out and to find out the aspects of aspects of Islamic theology in that tradition.Keywords : Aspects of Islamic Theology, Mapahukh Tradition Marriage